Processo de inserção dos refugiados nos municípios gaúchos pela ótica da New Public Governance - Postiglioni, Gabrielle Fagundes (2023)
The worsening political and economic crisis in Venezuela since 2014 has intensified the flow of Venezuelan citizens across the border in search of a place to start their lives over. This phenomenon points to new views and important issues for public management in discussions about strategies aimed at welcoming migrants and refugees. Faced with the complexity of forced migration, the Venezuelan population was extremely vulnerable and needed help from neighboring countries to guarantee their right to a dignified life. Faced with the great movement on the Brazil/Venezuela border, the Brazilian government proposed a multisectoral task force, known as Acolhida Operation, with a view to organizing the border and welcoming Venezuelan refugees. In addition to the action on the border, the Acolhida Operation undertakes efforts with the National Program for the Interiorization of Refugees, with the aim of distributing the new inhabitants to other regions of Brazil to reinsert them into society, providing opportunities and conditions to restructure their lives, as well as easing the situation at the border. Due to its proposed cooperation between governmental, non-governmental and civil society agents, this study's main objective is to understand the integration and socialization practices developed in the interiorization phase, for the reception of Venezuelan refugees in Brazilian municipalities. Therefore, the dimensions of New Public Governance (NPG) were theoretically identified, which is a model where the State adopts a plural, pluralistic, more democratic and participatory posture. Thus, it is no longer solely responsible for producing the public good, modifying the institutional relations between the public sector and society, articulating and expanding networks between internal and external organizations to the government to guarantee the provision of public services, as well as to act jointly for the identification and design of policies (OSBORNE, 2006). In view of this concept, the research is qualitative and exploratory, applied to representatives of municipalities in Rio Grande do Sul that received Venezuelan refugees between 2018 and 2020 through the interiorization program. Based on interviews with Brazilian Army volunteers who worked on the border and representatives of the cities of Cachoeirinha, Canoas and Esteio, the obtained content was analyzed from the perspective of the dimensions of the NPG. The results indicate a greater occurrence of practices that reflect Public Value, Co-production, Cooperation Networks and Efficiency and Effectiveness, from arrival at the border to reception in the municipalities. The Leadership and Accountability principles appear more strongly in the municipalities' practices. On the other hand, Deliberative Democracy and Displacement of Power, still latent, can be improved during the process, within the possibilities that the scenario presents. Looking at interagency action and the role of agents in building the integration of migrants and refugees from the perspective of the NPG can contribute to the maturation of public governance in practice. Furthermore, it is expected that this study represents an instrument for a better understanding of New Public Governance, contributing to the development of the discussion about this model by aligning theory and practice, based on the analysis of a process of such social and historical impact as the reception of Venezuelan refugees.